2004
DOI: 10.1021/jo048153i
|View full text |Cite
|
Sign up to set email alerts
|

Claimed 2,1-Benzisoxazoles Are Indazalones

Abstract: Claims, by two groups, to have prepared 2,1-benzisoxazole derivatives are corrected to show that the products are indazalones (5). In addition, a simple preparation of 3-oxy-substituted 2H-indazole, by an unrecognized method in the literature, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 5 publications
2
41
0
Order By: Relevance
“…Surprisingly, when we attempted to confirm the structure of this product by X-ray crystallography, it was found instead to be anthranil 6a . Although this was a surprising result based on our earlier work, which established that anthranils are not formed under Davis–Beirut reaction conditions, 10 serendipity, as noted by Hoye, 3 can “still play a pivotal role” in science.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Surprisingly, when we attempted to confirm the structure of this product by X-ray crystallography, it was found instead to be anthranil 6a . Although this was a surprising result based on our earlier work, which established that anthranils are not formed under Davis–Beirut reaction conditions, 10 serendipity, as noted by Hoye, 3 can “still play a pivotal role” in science.…”
Section: Resultsmentioning
confidence: 89%
“…NaOH in MeOH reported by Boduszek 9a and o -nitrosobenzaldehyde with benzylamine reported by Chen 9b were claimed to deliver anthranils, but our reinvestigation of those studies established that indazolones were produced instead. 10 Thus was born the Davis–Beirut reaction, which provides a robust method for constructing 2 H -indazoles from 2-nitrobenzylamines. 10 It is proposed that the Davis-Beirut reaction involves initial tautomerization of 2-nitrobenzylamine 1a by hydroxide to generate aci -nitro intermediate 1b (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kurth et al have demonstrated that the products of these reactions were in fact indazalones [263]. 9.5.2.3 By introduction of C-3 2,1-Benzisoxazole can be produced from the condensation of nitrobenzenes with benzyl cyanide in the presence of a base.…”
Section: Formation Of Bond 2-3mentioning
confidence: 99%
“…Addressing this need, we recently developed the Davis–Beirut reaction, 516 which is characterized by a noteworthy N , N -bond forming heterocyclization step, for the construction of a wide variety of 2 H -indazoles and indazolones (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%